2016
DOI: 10.3389/fphar.2016.00419
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin Inhibits Transforming Growth Factor β Induced Differentiation of Mouse Lung Fibroblasts to Myofibroblasts

Abstract: Transforming growth factor β (TGF-β) induced differentiation of lung fibroblasts to myofibroblasts is a key event in the pathogenesis of pulmonary fibrosis. This study aimed to evaluate the effect of curcumin on TGF-β induced differentiation of lung fibroblasts to myofibroblasts and explore the underlying mechanism. Mouse lung fibroblasts were cultured and treated with TGF-β2 and curcumin or rosiglitazone. Cell vitality was examined by MTT assay. The secretion of collagen-1 was assessed by ELISA. α smooth musc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 22 publications
(22 reference statements)
1
18
0
Order By: Relevance
“…Following curcumin treatment, the levels of both soluble and insoluble collagen were similar to their observed constitutive level for undifferentiated fibroblasts, attesting that curcumin down-regulated both TGF-β1 and collagen I expression and thus could impair or delay myofibrogenesis. In agreement with these results, it has been shown that curcumin inhibits both myofibrogenesis and collagen secretion in mice following bleomycin-induced lung injury 39,45 . Likewise, curcumin attenuated type I collagen production in an experimental pulmonary fibrosis in rats and showed beneficial antifibrotic effects in a rodent model of obstructive nephropathy 46,47 .…”
Section: Resultssupporting
confidence: 75%
“…Following curcumin treatment, the levels of both soluble and insoluble collagen were similar to their observed constitutive level for undifferentiated fibroblasts, attesting that curcumin down-regulated both TGF-β1 and collagen I expression and thus could impair or delay myofibrogenesis. In agreement with these results, it has been shown that curcumin inhibits both myofibrogenesis and collagen secretion in mice following bleomycin-induced lung injury 39,45 . Likewise, curcumin attenuated type I collagen production in an experimental pulmonary fibrosis in rats and showed beneficial antifibrotic effects in a rodent model of obstructive nephropathy 46,47 .…”
Section: Resultssupporting
confidence: 75%
“…The SMAD2/3 intracellular pathway was heavily implicated in TGF-β-induced fibrosis and is known as the canonical pathway ( He and Dai, 2015 ). Targeting the SMAD signaling pathway is a novel therapeutic approach to treating tissue fibrosis ( Wojcik et al., 2013 ; He and Dai, 2015 ; Liu et al., 2016 ; Tee et al., 2018 ; Zhang et al., 2018 ). In addition to activating the SMAD-dependent pathway, TGF-β can signal in a noncanonical manner, as exemplified in MAPK and NF-κB signaling, which together induce a complete TGF-β response ( Wu et al., 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…The inflammatory cells produced in response to TGF‐β, further induces epithelial cell injury and these cascades of events result in extracellular matrix (ECM) degradation and tissue scar formation . Several recent studies suggest that targeting the TGF signalling reduces the extent of PF in experimental models .…”
mentioning
confidence: 99%